Pengaruh Variasi Bentuk Permukaan Forging Dan Suhu Preheat Terhadap Kekuatan Tarik Friction Welding - Dimas Adi Perwira; Henry Widya Prasetya (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2020)
Most of the railway facilities use steel as the constituent material. The method of joining (joining methods) of steel materials, especially in the railroad industry, the most widely used is the welding technique (welding) so that knowledge of the welding process is very important for welding enginers and metallurgists as well as for designers, fabricators, users of welding results. The purpose of this study was to determine the tensile strength of the joint resulting from the friction welding method with variations in the shape of the forging surface and preheat temperature. The shape of the forging surface is 8 mm, 10 mm and 12 mm. Variations in preheat temperature of 200 C, 400 C and 600 C. The results showed the highest tensile strength of the friction weld joint with an average tensile stress value of 407, 48 MPa on the forging surface shape of 12 mm and a preheat temperature of 600 C. And the tensile strength of the joint The lowest friction welding with an average tensile stress value of 120 MPa on the forging surface shape of 8 mm and a preheat temperature of 200 C. Keyword: friction welding, forgings, preheat temperature